Berberine improved intestinal barrier function by modulating the intestinal microbiota in blunt snout bream (Megalobrama amblycephala) under dietary high-fat and high-carbohydrate stress. Issue 102 (July 2020) - Yu, Chengbing; Zhang, Jing; Qin, Qin; Liu, Jin; Xu, Jianxiong; Xu, Weina
Abstract: The study investigated whether dietary berberine supplementation could improve intestinal barrier against inflammation induced by high-fat and high-carbohydrate diets in blunt snout bream. Fish (average initial weight 44.83 ± 0.06 g) were fed with six kinds of diets (control, high-fat diet (10% lipid) and high-carbohydrate (43% nitrogen-free extract) diet, control/berberine, high-fat/berberine or high-carbohydrate/berberine) for 8 weeks, respectively. Feeding mode of berberine (50 mg/kg diet) was adopted to two-week interval. After feeding trial, fish growth performance and intestinal barrier function were estimated. The result showed that no significant interactions between diet and berberine in growth performance, whole body composition or protein utilization were observed ( P > 0.05 ). Specific growth rate (SGR) and feed conversion ratio (FCR) were significantly affected by berberine ( P < 0.05 ). Protein efficiency ratio (PER), nitrogen retention (NRE), fish whole-body lipid contents increased greatly in high-fat or high-carbohydrate diets ( P < 0.05 ). Significant interactions between diet and berberine were observed in fish intestinal barrier (physical, chemical, immunological and microbiological barriers) ( P < 0.05 ). High-fat and high-carbohydrate diets could increase significantly intestinal permeability and inflammatory response, decrease intestinal mucins gene expression levels, and make the intestinal microbiota out of balance ( P < 0.05 ). Berberine significantly inhibited inflammation response and modulated intestinal microflora profile ( P < 0.05 ). Taken together, berberine could alleviate intestinal barrier damage injured by high-fat or high-carbohydrate diet and improve the growth performance of blunt snout bream. Highlights: Dietary berberine supplementation at two-week interval feeding mode could protect intestinal barrier damage induced by high-fat diet and high-carbohydrate diet.